The leisure basis of caring - Stebbins, Robert A. (Frontiers in Psychology, 2023)
The social science literature on caring is long on application and short on concepts about its nature. In this latter capacity leisure is seldom mentioned as a context within which people care for others. This article examines the relationship of caring and compassion as expressed during free time in leisure activities. This has never been done, with the result that many contextual and motivational properties unique to leisure have been overlooked, and consequently, have been unavailable to both the theoretic and the practical sides of the sociology and psychology of compassion. The present article attempts to demonstrate that such oversight has denied this field some useful conceptual tools.